A method for preparing SiC / graphene composite material based on rapid joule heat realizing biomass carbon-silicon element collaborative conversion

CN122916147APending Publication Date: 2026-10-16UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611215503.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,目前以稻壳等生物质为原料制备SiC的研究较少,且大多仍沿用传统炉式高温碳热还原路线,整体反应周期长、能耗高,并在生物质复杂组分的条件下,易出现杂质残留、相组成与微观结构难以稳定控制等问题

Benefits of technology

[0025] This invention utilizes biomass as raw material to achieve the synergistic conversion and material utilization of carbon and silicon, thereby improving the overall utilization efficiency of solid waste resources. By constructing a synergistic conversion process of "pyrolysis-acid washing-rapid Joule heating-optional calcination," the simultaneous high-value utilization of carbon and silicon in rice husks is achieved, demonstrating significant advantages in technical effectiveness. On one hand, rapid Joule heating technology achieves ultra-fast heating and short-duration high-temperature reactions at millisecond to second levels, significantly shortening the reaction cycle and reducing energy consumption compared to traditional high-temperature carbothermal reduction processes. Simultaneously, under transient non-equilibrium conditions, it synergistically drives the carbothermal reduction of SiO2 and the graphitization of the carbon phase, successfully preparing a structurally controllable SiC/graphene composite material. This material can be flexibly converted into high-purity β-SiC through subsequent air calcination, enabling switchable product forms and performance control. On the other hand, pyrolysis oil and pyrolysis gas byproducts are simultaneously recovered during the pyrolysis stage, constructing an integrated pathway for material preparation and the synergistic utilization of energy resources, thus improving the overall resource efficiency and environmental friendliness of the process. In summary, this invention has significant technical effects and potential for widespread application in reducing energy burden, improving the controllability of material structure, and promoting the high-value utilization of biomass solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application provides a method for preparing SiC / graphene composite materials based on rapid Joule heat and realizing biomass carbon-silicon element collaborative conversion, and belongs to the technical field of waste biomass resource utilization. The application realizes synchronous high-value utilization of carbon and silicon elements in biomass by constructing a collaborative conversion process of "pyrolysis-acid pickling-rapid Joule heat-selective roasting", and has significant advantages in technical effect. On the one hand, the rapid Joule heat technology is used to realize ultrafast heating and short-time high-temperature reaction in milliseconds to seconds, and successfully prepare structure-controllable SiC / graphene composite materials, and the high-purity beta-SiC can be flexibly converted through subsequent air roasting, realizing the switchable product form and performance control. On the other hand, the pyrolysis oil and pyrolysis gas by-products are recovered synchronously in the pyrolysis stage, improving the resource efficiency and environmental friendliness of the overall process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of waste biomass resource utilization technology, and relates to a method for preparing SiC / graphene composite materials based on rapid Joule heating to achieve synergistic conversion of carbon and silicon elements in biomass. Background Technology

[0002] Silicon carbide (SiC) is widely used in wear-resistant components, power semiconductor device substrates, heat dissipation and heat conduction components, and functional material carriers in energy storage and electrochemical systems due to its high hardness, high thermal conductivity, wear resistance, corrosion resistance, and excellent high-temperature oxidation resistance. Traditional SiC preparation processes mainly include high-temperature carbothermal reduction (such as the Acheson method), chemical vapor deposition (CVD), polymer precursor pyrolysis (PDCs), and self-propagating high-temperature synthesis (SHS). Among these, the high-temperature carbothermal reduction method is the most mature and widely available in industrial applications. However, this method usually requires long-term holding at approximately 2000~2500℃, resulting in high energy consumption, long reaction cycles, and large equipment size. It also involves CO emissions and dust pollution, and the resulting product has relatively large grains and contains impurities, making it difficult to meet the requirements of low-carbon manufacturing and high-performance materials. While methods such as CVD and PDCs can obtain SiC materials with high purity or controllable morphology, they have problems such as high equipment investment, complex processes, high precursor costs or limited yields, which are not conducive to large-scale and low-cost preparation.

[0003] my country's agricultural and industrial production generates a large amount of organic solid waste rich in carbon and silicon each year, such as rice husks, straw, sawdust, and agricultural and forestry residues. However, their utilization rate is generally low, and they are often directly burned or composted, resulting in resource waste and environmental emissions. Taking rice husks as an example, they contain approximately 45-50 wt% carbon and 15-20 wt% SiO2, naturally possessing a carbon-silicon synergistic source characteristic, theoretically making them an ideal raw material for preparing SiC and carbon-silicon composites. However, current research on SiC preparation using biomass such as rice husks is limited, and most methods still follow the traditional furnace-type high-temperature carbothermal reduction route. This results in long reaction cycles, high energy consumption, and, under the complex composition of biomass, problems such as impurity residues and difficulty in stable control of phase composition and microstructure easily arise. Furthermore, most processes only focus on the preparation of solid products, neglecting the utilization of byproducts such as pyrolysis oil and pyrolysis gas obtained simultaneously during pyrolysis, leading to a need to improve the comprehensive utilization rate of resources. Summary of the Invention

[0004] In view of this, the purpose of this invention is to provide a method for preparing SiC / graphene composite materials based on rapid Joule heating for the synergistic conversion of carbon and silicon elements in biomass. This method achieves the simultaneous conversion of SiO2 and carbon sources in rice husks through a multi-stage synergistic process of "pyrolysis-acid washing-rapid Joule heating-optional calcination," preparing SiC / graphene composite materials and further obtaining high-purity SiC materials, while also taking into account the recovery and utilization of byproducts such as pyrolysis oil and pyrolysis gas.

[0005] To achieve this objective, the present invention adopts the following technical solution:

[0006] In a first aspect, the present invention provides a method for preparing SiC / graphene composite materials based on rapid Joule heating to achieve synergistic conversion of carbon and silicon elements in biomass, comprising the following steps:

[0007] (1) The biomass is pyrolyzed under an inert atmosphere to obtain pyrolytic carbon;

[0008] (2) The pyrolytic carbon is acid-washed to remove impurities, washed and dried to obtain pretreated carbon material;

[0009] (3) The pretreated carbon material is subjected to rapid Joule heat treatment by capacitor flash evaporation, and transient heating is performed to raise the temperature of the pretreated carbon material to 2800~3800℃, and then cooled to obtain graphene-doped SiC composite material.

[0010] or

[0011] The pretreated carbon material was subjected to rapid Joule heating using a DC power supply to raise the temperature to 2000~3000℃ and hold it thereafter, and then cooled to obtain a graphene-doped SiC composite material.

[0012] Preferably, the pyrolysis treatment is performed at a temperature of 450~550℃ for a time of 1~3 h.

[0013] Preferably, the inert atmosphere is nitrogen or an oxygen-free atmosphere.

[0014] Preferably, in step (1), the gaseous and liquid products generated during the pyrolysis process are collected simultaneously to obtain pyrolysis gas and pyrolysis oil, respectively.

[0015] Preferably, the pickling uses an inorganic acid solution with a concentration of 0.5~2.0 mol / L.

[0016] Preferably, the inorganic acid in the inorganic acid solution includes any one or more of hydrochloric acid, sulfuric acid, or nitric acid.

[0017] Preferably, the capacitor flash evaporation involves 5 to 10 flashes and a flash voltage of 140 to 180 V.

[0018] Preferably, the Joule heating current of the DC power supply is 40~80 A, and the heat preservation time is 5~30 s.

[0019] Preferably, the biomass includes any one of rice husks, wheat straw, corn cobs, or reed stalks.

[0020] In this invention, the SiC / graphene composite material prepared according to the above method has SiC as cubic β-SiC and graphene as defect-rich multilayer graphene, with SiC distributed on the surface or at the interface of the graphene.

[0021] In a second aspect, the present invention provides a method for preparing high-purity cubic SiC material, including steps (1) to (3) of the above method, preferably further including calcination treatment in air atmosphere after obtaining SiC / graphene composite material.

[0022] Preferably, the calcination treatment is carried out at a temperature of 600~800℃ for 1~4 hours.

[0023] The present invention also provides a high-purity cubic SiC material prepared according to the above preparation method.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0025] This invention utilizes biomass as raw material to achieve the synergistic conversion and material utilization of carbon and silicon, thereby improving the overall utilization efficiency of solid waste resources. By constructing a synergistic conversion process of "pyrolysis-acid washing-rapid Joule heating-optional calcination," the simultaneous high-value utilization of carbon and silicon in rice husks is achieved, demonstrating significant advantages in technical effectiveness. On one hand, rapid Joule heating technology achieves ultra-fast heating and short-duration high-temperature reactions at millisecond to second levels, significantly shortening the reaction cycle and reducing energy consumption compared to traditional high-temperature carbothermal reduction processes. Simultaneously, under transient non-equilibrium conditions, it synergistically drives the carbothermal reduction of SiO2 and the graphitization of the carbon phase, successfully preparing a structurally controllable SiC / graphene composite material. This material can be flexibly converted into high-purity β-SiC through subsequent air calcination, enabling switchable product forms and performance control. On the other hand, pyrolysis oil and pyrolysis gas byproducts are simultaneously recovered during the pyrolysis stage, constructing an integrated pathway for material preparation and the synergistic utilization of energy resources, thus improving the overall resource efficiency and environmental friendliness of the process. In summary, this invention has significant technical effects and potential for widespread application in reducing energy burden, improving the controllability of material structure, and promoting the high-value utilization of biomass solid waste. Attached Figure Description

[0026] Figure 1 The graph shows the liquid phase products from the pyrolysis process in Example 1 obtained by gas chromatography-mass spectrometry (GC-MS).

[0027] Figure 2The graphs shown are the current curve and the actual temperature curve recorded using an infrared thermometer when the input voltage is 160 V in Example 2.

[0028] in, Figure 2 The 'a' in the figure corresponds to the current curve when the input voltage is 160 V. Figure 2 In the figure, 'b' corresponds to the actual temperature curve recorded using an infrared thermometer.

[0029] Figure 3 This is an X-ray photoelectron spectroscopy (XPS) image of the material after flash evaporation in Example 2;

[0030] in, Figure 3 In the image, 'a' represents the XPS-Si spectrum of the biochar before the reaction. Figure 3 In the image, b represents the XPS-Si spectrum of the product after the reaction. Figure 3 In the figure, c represents the XPS-C spectrum of the product after the reaction;

[0031] Figure 4 The image shows the Raman spectrum of the material after flash evaporation in Example 2.

[0032] Figure 5 The graph shows the BET specific surface area test results of the flash-evaporated material in Example 2.

[0033] in, Figure 5 In the figure, 'a' represents the adsorption-desorption curve of the specific surface area of ​​the material after flash evaporation. Figure 5 In the diagram, b represents the pore size distribution of the material after flash evaporation.

[0034] Figure 6 The images shown are scanning electron microscope (SEM) images and energy dispersive X-ray spectroscopy (EDS) characterization results of the flash-evaporated material in Example 2.

[0035] Figure 7 The images show the X-ray diffraction (XRD) characterization results of the crystalline phase in the solid residue after flash evaporation experiments under different input voltages and different FJH cycles in Example 2.

[0036] in, Figure 7 In the image, 'a' corresponds to the X-ray diffraction (XRD) characterization results of the crystalline phase under different input voltages; Figure 7 In the image, b corresponds to the X-ray diffraction (XRD) characterization results of the crystalline phase under different FJH cycles;

[0037] Figure 8 Raman images of the material after high-temperature heating in Example 3;

[0038] Figure 9The graphs show the current curves when the temperature rises to 2200℃ and is maintained at that temperature in Example 3, and the actual temperature curves recorded using an infrared thermometer.

[0039] in, Figure 9 The current curve for 'a' in the figure corresponds to the temperature rising to 2200℃ and being kept at that temperature. Figure 9 In the figure, 'b' corresponds to the actual temperature curve recorded using an infrared thermometer.

[0040] Figure 10 The images show the XRD characterization results of the crystalline phase in the solid residue after Joule heating experiments at different heating temperatures and times in Example 3.

[0041] in, Figure 10 In the image, 'a' corresponds to the X-ray diffraction (XRD) characterization results of the crystalline phase under different heating times; Figure 10 In the image, b corresponds to the X-ray diffraction (XRD) characterization results of the crystalline phase at different heating temperatures;

[0042] Figure 11 SEM images of the products heated at 2200°C for 5 s and 20 s in Example 3;

[0043] in, Figure 11 In this context, 'a' corresponds to heating at 2200℃ for 5 seconds. Figure 11 In this context, 'b' corresponds to heating at 2200℃ for 20 seconds.

[0044] Figure 12 The images show the HRTEM characterization results of the products heated at 2200°C for 5 s and 20 s in Example 3.

[0045] in, Figure 12 Images a and b in the image correspond to TEM images of SiC particles heated at 2200℃ for 5 s. The images show 0.25 nm lattice fringes of β-SiC. Figure 12 c and d in the image correspond to TEM images of SiC nanowire products heated at 2200℃ for 5 s. Figure 12 The 'e' in the image corresponds to a TEM image of SiC particle products heated at 2200℃ for 20 s. Figure 12 The f in the image corresponds to the TEM image of the SiC nanowire product heated at 2200℃ for 20s.

[0046] Figure 13 XRD image of the product after direct Joule heat flash evaporation of rice husks in Comparative Example 1.

[0047] Figure 14 XRD image of the product of unwashed rice husk carbon after flash heating in Comparative Example 2;

[0048] Figure 15 This is a comparison of the XRD patterns of the products before and after air calcination in Example 4;

[0049] Figure 16 The image shows the XRD pattern of the product obtained by joule heating of wheat straw in Example 5.

[0050] Figure 17 The image shows the XRD pattern of the product after Joule heating of corn cobs in Example 6.

[0051] Figure 18 The image shows the XRD pattern of the product after Joule heating of reed stalks in Example 7.

[0052] Figure 19 The graph shows the cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) test results of the graphene / β-SiC composite material prepared in Example 8 as a supercapacitor electrode material.

[0053] in, Figure 19 In the figure, 'a' represents the constant current charge-discharge curves at different sweep rates. Figure 19 In the figure, b represents the cyclic voltammetry curve. Detailed Implementation

[0054] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0055] In view of the fact that there are few studies on the preparation of SiC from biomass such as rice husks in the existing technology, and most of them still rely on the traditional furnace high-temperature carbothermal reduction route, which has problems such as long reaction cycle, high energy consumption, poor product quality and insufficient utilization of by-products, this invention uses biomass as raw material to prepare SiC / graphene composite materials through pyrolysis, acid washing pretreatment and rapid Joule thermal flash heating, and can further obtain high-purity SiC materials, while taking into account the recycling of by-products such as pyrolysis oil and pyrolysis gas.

[0056] The technical solution of the present invention will now be described in detail.

[0057] This invention provides a method for preparing SiC / graphene composite materials based on rapid Joule heating and synergistic conversion of biomass carbon and silicon, comprising the following steps:

[0058] (1) The biomass is pyrolyzed under an inert atmosphere to obtain pyrolytic carbon;

[0059] (2) The pyrolytic carbon is acid-washed to remove impurities, washed and dried to obtain pretreated carbon material;

[0060] (3) The pretreated carbon material is subjected to rapid Joule heat treatment by capacitor flash evaporation, and transient heating is performed to raise the temperature of the pretreated carbon material to 2800~3800℃, and then cooled to obtain graphene-doped SiC composite material.

[0061] or

[0062] The pretreated carbon material was subjected to rapid Joule heating using a DC power supply to raise the temperature to 2000~3000℃ and hold it thereafter, and then cooled to obtain a graphene-doped SiC composite material.

[0063] According to the present invention, biomass is first subjected to pyrolysis under an inert atmosphere to obtain pyrolytic carbon.

[0064] In this invention, the biomass is preferably silicon-rich agricultural and forestry waste, such as rice husks, wheat straw, corn cobs, or reed stalks.

[0065] In this invention, the temperature of the pyrolysis treatment is 450~550℃, such as 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, 510℃, 520℃, 530℃, 540℃ or 550℃, etc.; the time is 1~3 h, such as 1 h, 1.5 h, 2 h, 2.5 h or 3 h, etc.

[0066] In this invention, the inert atmosphere is either nitrogen or an oxygen-free atmosphere, and the yield and products differ little under the two atmospheres.

[0067] In some embodiments of the present invention, it is preferable to pulverize and sieve the naturally air-dried biomass to ensure uniform particle size distribution. Then, the treated biomass is placed in a quartz crucible and fed into a pyrolysis furnace, where it is heated at 5–12 °C / min under a nitrogen or oxygen-deficient atmosphere. -1 Preferably 10 ℃·min -1 The pyrolysis reaction is completed by heating to 450~550℃ and holding for 1~3 hours. The solid residue in the furnace is the pyrolytic carbon.

[0068] In some preferred embodiments of the present invention, while performing the pyrolysis treatment in step (1) above, it is also preferable to collect the gaseous products and liquid products generated during the pyrolysis process to obtain pyrolysis gas and pyrolysis oil respectively.

[0069] Then, according to the present invention, the pyrolytic carbon is acid-washed to remove impurities, washed and dried to obtain pretreated carbon material.

[0070] In this invention, the pickling process uses an inorganic acid solution with a concentration of 0.5~2.0 mol / L. The inorganic acid in the solution includes any one or more of hydrochloric acid, sulfuric acid, or nitric acid.

[0071] The aforementioned 0.5~2.0 mol / L can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, or 2.0 mol / L, etc.

[0072] In some embodiments of the present invention, pyrolytic carbon solid is preferably added to an inorganic acid solution with a solid-liquid ratio of approximately 1:5 to 1:20 (g:mL), preferably 1:8 to 1:18 (g:mL), and more preferably 1:10 to 1:15 (g:mL). The solution is then soaked and sonicated at room temperature for 1 to 5 hours, preferably 4 hours, to remove inorganic salts and metallic impurities. After acid washing, the sample is thoroughly washed with deionized water until the pH of the filtrate is close to neutral. The solid sample is then dried in a forced-air oven at 50 to 70°C, preferably 60°C, for 8 to 15 hours, preferably 12 hours, to obtain a pretreated carbon material with significantly reduced ash content and containing uniformly distributed SiO2 and carbon phases.

[0073] Then, according to the present invention, the pretreated carbon material is subjected to rapid Joule heat treatment.

[0074] In some embodiments of the present invention, the pretreated carbon material is preferably subjected to rapid Joule heat treatment by capacitor flash evaporation, which transiently heats the pretreated carbon material to 2800~3800°C, and then cools it to obtain a graphene-doped SiC composite material.

[0075] The capacitor flash evaporation process involves 5 to 10 flashes, such as 5, 6, 7, 8, 9, or 10 flashes; the flash voltage is 140 to 180 V, generating high-current pulses, such as 140 V, 145 V, 150 V, 155 V, 160 V, 165 V, 170 V, 175 V, or 180 V.

[0076] In some embodiments of the present invention, it is preferred to flash evaporate 5 times at 160 V.

[0077] In other embodiments of the present invention, the pretreated carbon material is preferably subjected to rapid Joule heating using a DC power supply, raising the temperature of the pretreated carbon material to 2000-3000°C and holding it at that temperature, followed by cooling to obtain a graphene-doped SiC composite material. The aforementioned 2000-3000°C can be 2000°C, 2100°C, 2200°C, 2300°C, 2400°C, 2500°C, 2600°C, 2700°C, 2800°C, 2900°C, or 3000°C, etc.

[0078] The Joule heating current of the DC power supply is 40~80 A, such as 40 A, 45 A, 50 A, 55 A, 60 A, 65 A, 70 A, 75 A, or 80 A. The heat preservation time is 5~30 s, such as 5 s, 8 s, 10 s, 12 s, 15 s, 18 s, 20 s, 22 s, 25 s, 28 s, or 30 s.

[0079] This explains that short-term high-temperature holding facilitates the complete carbothermic reduction of SiO2 and promotes the crystallization and growth of SiC grains, while simultaneously enabling the carbon phase to fully graphitize and form highly ordered graphene. Holding at temperatures above 2200℃ for 5 seconds allows for rapid carbothermic reduction of SiO2 in the precursor, generating cubic β-SiC nanocrystals, while simultaneously enabling the carbon phase to fully graphitize and form highly ordered graphene.

[0080] In the aforementioned rapid Joule heat treatment process, the material is rapidly heated in a non-equilibrium thermal field by capacitor flash evaporation or DC power supply Joule heating. The biomass-derived silicon oxide undergoes a carbothermic reduction reaction with carbon, while the carbon phase undergoes rapid graphitization, resulting in graphene-doped SiC composite material.

[0081] In this invention, the SiC / graphene composite material prepared according to the above method has SiC as cubic β-SiC and graphene as defect-rich multilayer graphene, with SiC distributed on the surface or at the interface of the graphene.

[0082] In some other embodiments of the present invention, after obtaining the SiC / graphene composite material, a calcination treatment is performed in an air atmosphere to remove the graphene carbon phase and obtain high-purity β-SiC.

[0083] The calcination temperature is 600~800℃, such as 600℃, 620℃, 640℃, 660℃, 680℃, 700℃, 720℃, 740℃, 760℃, 780℃ or 800℃, etc.; the time is 1~4 h, such as 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h or 4 h, etc.

[0084] The present invention also provides the above-mentioned high-purity β-SiC, which can be used as a raw material for high-temperature structural ceramics, a base material for wear-resistant and corrosion-resistant coatings, or a filler for high thermal conductivity composite materials, providing a material basis for its application in electronic packaging, heat dissipation devices and other fields.

[0085] To further illustrate the present invention, the following embodiments provide a detailed description. Unless otherwise specified, all experimental materials used in the following embodiments of the present invention are commercially available products.

[0086] Example 1

[0087] Naturally air-dried rice husks are selected, crushed, and then sieved through a 60-100 mesh screen to remove excessively large or fine particles, ensuring a uniform particle size distribution. The processed rice husks are then placed in a quartz crucible and fed into a pyrolysis furnace at 10 °C / min under a nitrogen or oxygen-deficient atmosphere. -1 The temperature was raised to 500℃ and held for 2 hours to complete the pyrolysis reaction. The volatiles produced during pyrolysis were collected after cooling in a condenser to obtain liquid bio-oil. The components of the pyrolysis oil are as follows: Figure 1 As shown, the precursor is mainly composed of monocyclic aromatic hydrocarbons, with high carbon content and low nitrogen content. Uncondensed gas is discharged and recycled through the gas outlet, realizing the resource utilization of gaseous and liquid byproducts. The residual solid product in the furnace is pyrolytic carbon solid. After the furnace temperature naturally cools to room temperature, the pyrolytic solid is removed and added to a 1 M hydrochloric acid solution with a solid-liquid ratio of approximately 1:10 (g:mL). The solution is then soaked and sonicated at room temperature for 4 hours to remove inorganic salts and metallic impurities. After acid washing, the sample is thoroughly washed with deionized water until the pH of the filtrate is close to neutral. The solid sample is then dried in a 60℃ forced-air oven for 12 hours, yielding a rice husk-based carbon-silicon precursor powder with significantly reduced ash content and uniformly distributed SiO2 and carbon phases. This precursor can be directly used for flash Joule heat treatment.

[0088] Example 2

[0089] This embodiment, based on the rice husk-based carbon-silicon precursor described in Example 1, prepares graphene-doped SiC composite materials using the FJH process of capacitive charge-discharge and multiple flash evaporation. The precursor powder from Example 1 is uniformly packed between two conductive graphite electrodes in a graphite paper quartz tube and placed in a rapid Joule heat treatment apparatus. A 160 V pulse voltage is applied in a vacuum environment for flash heating, followed by intermittent cooling for several seconds after the discharge ends. This flash evaporation is repeated five times, allowing the precursor to repeatedly undergo ultrafast heating-cooling processes on a millisecond timescale. The peak temperature is estimated to reach approximately 3000℃. The current curve and actual temperature curve for a single flash evaporation process are shown below. Figure 2 As shown, under these non-equilibrium high-temperature conditions, SiO2 in the precursor undergoes rapid carbothermic reduction to generate cubic β-SiC nanocrystals, while the carbon phase undergoes rapid graphitization and reconstruction into a multilayer graphene framework, thus obtaining graphene / β-SiC composite powder.

[0090] like Figure 3 As shown, XPS testing revealed distinct peaks for Si-C bonds and graphitic carbon bonds in the product; Raman spectroscopy showed... Figure 4 As shown, the D and G bands exhibit characteristic vibrational peaks of β-SiC, indicating the synergistic formation of graphene and SiC. SEM images of the product are shown below. Figure 6 As shown, SiC and graphene are repeatedly doped, with most of the SiC crystals encased in residual carbon, and only a small portion exposed. For example... Figure 5 As shown, the specific surface area of ​​the material remained at tens of m² through BET specific surface area testing. 2 ·g -1 The pore structure is mainly mesoporous, indicating that the composite material has both good electrical conductivity and a certain porosity, and can be used as an electrode material or conductive framework.

[0091] Experiments were conducted under different voltages and flash evaporation cycles, and the XRD patterns of the products were as follows: Figure 7 As shown in Table 1, the yields are as follows. When the flash voltage is too low or the number of flashes is insufficient, the system cannot reach the transient high temperature and interfacial energy required for the formation of SiC and graphene. Repeating flash evaporation five times at 160 V can suppress structural damage while ensuring the non-equilibrium high-temperature reaction, which is a key parameter condition for achieving the ideal composite structure.

[0092] Table 1

[0093] Reaction voltage / V Number of reactions / times Composite material yield / % SiC yield / % 160 5 30 10 160 10 28 14.8 180 5 20 9.2

[0094] Example 3

[0095] This embodiment, based on the precursor described in Example 1, prepares a graphene-doped SiC composite material by maintaining a certain heating time at a high temperature. The precursor powder from Example 1 is uniformly packed between two conductive graphite electrodes in a graphite paper quartz tube and placed in a rapid Joule heat treatment apparatus. A current of approximately 75 A is applied in a vacuum environment for Joule heating, with the holding time controlled at 20 s, allowing the precursor to reach 2200°C within a second-scale timescale, followed by rapid cooling, achieving rapid heating and cooling. The current and temperature during the heating process are as follows: Figure 9 As shown, short-term high-temperature holding facilitates the complete carbothermic reduction of SiO2 and promotes the crystallization and growth of SiC grains, while simultaneously enabling the carbon phase to fully graphitize and form highly ordered graphene. Holding at 2200℃ for 20 s allows for rapid carbothermic reduction of SiO2 in the precursor to generate cubic β-SiC nanocrystals, while simultaneously enabling the carbon phase to fully graphitize and form highly ordered graphene. Figure 8 As shown, Raman spectroscopy can also characterize the characteristic peaks of graphene and SiC.

[0096] Comparative experiments were conducted using different flash rates, holding times, and temperature conditions. The results showed that the SiC conversion rate increased with increasing temperature and holding time. Figure 10 As shown, heating at 2200℃ for 5 seconds can completely transform it into cubic β-SiC nanocrystals. Meanwhile, as... Figure 11 As shown, SEM characterization revealed that increasing the temperature and extending the heating time reduced the particle size. Figure 12 As shown (where, Figure 12 Images a and b in the image correspond to TEM images of SiC particles heated at 2200℃ for 5 s. The images show 0.25 nm lattice fringes of β-SiC. Figure 12 c and d in the image correspond to TEM images of SiC nanowire products heated at 2200℃ for 5 s. Figure 12 The 'e' in the image corresponds to a TEM image of SiC particle products heated at 2200℃ for 20 s. Figure 12 In the image, f corresponds to the TEM image of the SiC nanowire product heated at 2200℃ for 20 s. Clear β-SiC lattice fringes can be seen in the HRTEM image. The interplanar spacing at 0.25 nm corresponds to the (111) plane of β-SiC, while that at 0.15 nm corresponds to the (220) plane. Simultaneously, with increasing heating time, the particle size decreases from 100+ nm to 10 nm. Furthermore, SiC nanowires are generated in the product; with increasing heating time, the proportion of nanowires increases, and the particle size decreases. In addition, increasing temperature and extending heating time also affect the yield. Table 2 shows the yield comparison for different reaction times and temperatures.

[0097] Table 2

[0098] reaction time / s Reaction temperature / ℃ Graphene / SiC yield SiC yield 5 2200 56 30.2 5 2400 45 22.5 5 2600 40 26 10 2200 50 30 20 2200 45 27

[0099] Comparative Example 1

[0100] To investigate the role of the pre-carbonization step in the process of this invention, untreated raw rice husk powder was directly loaded into a flash Joule heating apparatus, and flash heating was performed under a vacuum atmosphere with a pulsed voltage of 160 V, using the same power supply method as in Example 2. Figure 13As shown, XRD analysis of the obtained product revealed only a small number of broadened amorphous carbon peaks and weak β-SiC diffraction peaks, with noticeable residual SiO2 peaks still present. Compared to the stable carbon framework obtained by pyrolysis at 500℃ in Examples 1-3, this comparative sample, due to the lack of devolatilization and carbonization of organic components such as hemicellulose and lignin in the original rice husk, underwent violent vaporization and decomposition during flash heating. This resulted in severely uneven thermal stress and current distribution in the system, making it difficult to form a stable carbon-silicon interface reaction environment, thereby inhibiting β-SiC formation and damaging the material structure. These results indicate that pre-carbonization treatment is a necessary condition for achieving synergistic carbon-silicon conversion and structural stability control, and cannot be omitted.

[0101] Comparative Example 2

[0102] To illustrate the importance of acid washing pretreatment in the process of this invention, Comparative Example 2 was set up. Rice husk solids obtained after pyrolysis in Example 1 were selected and, without any acid washing treatment, were directly dried and packed into a flash Joule heating device. Under the same conditions as in Example 2, a pulse voltage of 160 V was applied for 5 flash evaporation treatments. The XRD test results of the samples obtained after flash heating are as follows: Figure 14 As shown, besides the diffraction peaks of β-SiC and a small amount of graphitic carbon, there are still strong diffraction peaks of impurity phases, presumably residual metal oxides and incompletely reacted SiO2. Compared with Example 2, this comparative example shows that if the acid washing step is omitted, mineral impurities will cause local overheating and uneven current distribution during flash heating, inhibiting SiO2 reduction and carbon phase graphitization, thereby damaging the structural integrity and electrical properties of the material. This confirms that acid washing is a key process step in achieving high-performance graphene / SiC composite materials in this invention.

[0103] Example 4

[0104] This embodiment, based on Example 3, selectively removes the graphene phase through medium-temperature air calcination to prepare high-purity cubic β-SiC powder. The graphene / SiC composite powder obtained in Example 3 is uniformly spread in a ceramic boat and placed in a muffle furnace, calcined at 3°C / min in an air atmosphere. -1 The temperature was raised to 700℃ at a controlled heating rate and held for 2 hours, then allowed to cool naturally to room temperature. Since graphene and amorphous carbon can be gradually oxidized to CO2 in air within the range of 600–700℃ and discharged from the system, and β-SiC exhibits good thermal stability at this temperature, the carbon phase in the sample was essentially removed after calcination. Figure 15 As shown, XRD test results indicate that the product retains only the characteristic diffraction peaks of β-SiC, while the graphite carbon (002) peak disappears. This powder can be used as a raw material for high-temperature structural ceramics, a base material for wear-resistant and corrosion-resistant coatings, or a filler for high thermal conductivity composite materials, providing a material basis for its application in electronic packaging, heat dissipation devices, and other fields.

[0105] Example 5

[0106] This embodiment illustrates the applicability of the process of the present invention to other silicon-rich agricultural and forestry wastes, using wheat straw as an example. Naturally dried straw is selected, crushed, and passed through an 80-mesh sieve. The powder passing through the sieve is placed in a quartz boat and, under the same conditions as in Example 1, heated at 10 °C·min under nitrogen protection. -1 The temperature was raised to 500℃ and held for 2 hours. Pyrolysis oil and combustible gas were simultaneously collected using a condenser and oil-gas separation device to obtain wheat straw-based pyrolysis char. Subsequently, it was acid-washed with 1 M hydrochloric acid for 4 hours, washed until neutral, and dried to obtain straw-based carbon-silicon precursor powder. This precursor was packed into a flash Joule heating apparatus, heated to 2200℃ under vacuum, and held for 10 seconds. Figure 16 As shown, XRD analysis of the product revealed the presence of characteristic diffraction peaks of β-SiC in the sample. Raman spectroscopy showed the coexistence of graphene D and G peaks with characteristic peaks of β-SiC, demonstrating that native SiO2 and carbon in wheat straw can also be synergistically converted into a graphene / SiC composite structure under flash heating conditions. Although the β-SiC content and grain size differ slightly from the rice husk system due to variations in raw material ash and SiO2 content, the overall process route remains consistent, indicating that this invention is applicable to various silicon-rich biomass, and that high-value synergistic carbon-silicon conversion can be achieved by adjusting the voltage and energizing time.

[0107] Example 6

[0108] This embodiment illustrates the applicability of the process of the present invention to other silicon-rich agricultural and forestry wastes, using corn cobs as an example. Naturally dried corn cobs are selected, crushed, and passed through a 100-mesh sieve. The sieved powder is placed in a quartz boat and, under the same conditions as in Example 1, heated at 10 °C / min under nitrogen protection. -1 The temperature was raised to 500℃ and held for 2 hours. Pyrolysis oil and combustible gas were simultaneously collected using a condenser and oil-gas separation device to obtain corn cob-based pyrolysis char. Subsequently, it was acid-washed with 1 M hydrochloric acid for 4 hours, washed until neutral, and dried to obtain corn cob-based carbon-silicon precursor powder. This precursor was packed into a flash Joule heating apparatus, heated to 2200℃ under vacuum, and held for 10 seconds. Figure 17 As shown, XRD analysis of the product revealed characteristic diffraction peaks of β-SiC in the sample, demonstrating that native SiO2 and carbon in corn cobs can also be synergistically converted into a graphene / SiC composite structure under flash heating conditions. Although the β-SiC content and grain size differ slightly from the rice husk system due to variations in raw material ash and SiO2 content, the overall process route remains consistent, indicating that this invention is applicable to various silicon-rich biomass, and that high-value synergistic carbon-silicon conversion can be achieved by adjusting the voltage and energizing time.

[0109] Example 7

[0110] This embodiment illustrates the applicability of the process of the present invention to other silicon-rich agricultural and forestry wastes, using reed stalks as an example. Naturally dried reed stalks are selected, crushed, and passed through a 100-mesh sieve. The powder passing through the sieve is placed in a quartz boat and, under the same conditions as in Example 1, heated at 10 °C·min under nitrogen protection. -1 The temperature was raised to 500℃ and held for 2 hours. Pyrolysis oil and combustible gas were simultaneously collected using a condenser and oil-gas separation device to obtain reed stalk-based pyrolysis char. Subsequently, it was acid-washed with 1 M hydrochloric acid for 4 hours until neutral and then dried to obtain reed stalk-based carbon-silicon precursor powder. This precursor was packed into a flash Joule heating apparatus, heated to 2200℃ under vacuum, and held for 10 seconds. Figure 18 As shown, XRD analysis of the product revealed characteristic diffraction peaks of β-SiC in the sample, demonstrating that native SiO2 and carbon in reed stalks can also be synergistically converted into a graphene / SiC composite structure under flash heating conditions. Although the β-SiC content and grain size differ slightly from the rice husk system due to variations in raw material ash and SiO2 content, the overall process route remains consistent, indicating that this invention is applicable to various silicon-rich biomass, and that high-value synergistic carbon-silicon conversion can be achieved by adjusting the voltage and energizing time.

[0111] Example 8

[0112] This embodiment illustrates the application of the graphene / β-SiC composite material prepared in Example 2 or Example 3 as an electrode material for supercapacitors. The above composite material powder was selected and mixed with a conductive agent (such as acetylene black) and a binder (such as polyvinylidene fluoride, PVDF) at a mass ratio of 8:1:1. An appropriate amount of NMP solvent was added, and the mixture was ultrasonically dispersed to form a uniform slurry. The slurry was then uniformly coated onto a nickel foam or carbon paper current collector, controlling the active material loading at 5 mg·cm³. -2 Within the specified range, the working electrode was obtained by vacuum drying at 60℃ followed by pressing. In the three-electrode system, Hg / HgO was used as the reference electrode, a platinum sheet as the counter electrode, and 6 M KOH aqueous solution was used as the electrolyte. Cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS) were performed on the electrode. Figure 19 As shown, the results indicate that in the range of 5–100 mV·s -1 At the scan rate, the CV curve exhibits a nearly rectangular shape and no obvious redox peaks, demonstrating typical characteristics of electric double-layer capacitance; at 0.05~1 A·g -1 Within the current density range, the GCD curves of the electrodes exhibit good symmetry, and the calculated specific capacitance can reach tens to hundreds of F·g. -1The levels are higher than those of rice husk carbon alone or SiC material electrodes alone. These results demonstrate that the graphene / SiC composite material obtained in this invention has good application prospects in the field of energy storage devices.

[0113] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing SiC / graphene composite materials based on rapid Joule heating for the synergistic conversion of biomass carbon and silicon, characterized in that, Includes the following steps: (1) The biomass is pyrolyzed under an inert atmosphere to obtain pyrolytic carbon; (2) The pyrolytic carbon is acid-washed to remove impurities, washed and dried to obtain pretreated carbon material; (3) The pretreated carbon material is subjected to rapid Joule heat treatment by capacitor flash evaporation, and transient heating is performed to raise the temperature of the pretreated carbon material to 2800~3800℃, and then cooled to obtain graphene-doped SiC composite material. or The pretreated carbon material was subjected to rapid Joule heating using a DC power supply to raise the temperature to 2000~3000℃ and hold it thereafter, and then cooled to obtain a graphene-doped SiC composite material.

2. The method according to claim 1, characterized in that, The pyrolysis treatment is performed at a temperature of 450~550℃ for a time of 1~3 h. The inert atmosphere is nitrogen or an oxygen-free atmosphere; In step (1), the gaseous and liquid products generated during the pyrolysis process are collected to obtain pyrolysis gas and pyrolysis oil, respectively.

3. The method according to claim 1 or 2, characterized in that, The pickling process uses an inorganic acid solution with a concentration of 0.5~2.0 mol / L; The inorganic acid in the inorganic acid solution includes any one or more of hydrochloric acid, sulfuric acid, or nitric acid.

4. The method according to claim 1, characterized in that, The capacitor flash evaporation process involves 5 to 10 flashes and a flash voltage of 140 to 180 V.

5. The method according to claim 1, characterized in that, The current for Joule heating of the DC power supply is 40~80 A, and the heat preservation time is 5~30 s.

6. The method according to claim 1, characterized in that, The biomass includes any one of rice husks, wheat straw, corn cobs, or reed stalks.

7. The SiC / graphene composite material prepared according to claim 1, characterized in that, SiC is cubic β-SiC, and graphene is defect-rich multilayer graphene, with SiC distributed on the surface or at the interface of graphene.

8. A method for preparing high-purity cubic SiC material, comprising steps (1) to (3) of the method according to any one of claims 1 to 6, characterized in that, After obtaining the SiC / graphene composite material, a calcination process is also performed in an air atmosphere.

9. The preparation method according to claim 8, characterized in that, The calcination process is carried out at a temperature of 600-800℃ for 1-4 hours.

10. The high-purity cubic SiC material prepared by the preparation method according to claim 8 or 9.